Synchronous Web-based Learning during COVID -19 Pandemic: A Survey on Library and Information Science Students of Bangladesh - Roslina Othman; Debarshi Mukherjee; Sk Mamun Mostofa; Khandakar Kamrul Hasan (Journal of Information Technology Management, 2021)
The coronavirus pandemic has compelled academic institutions across the globe to initiate online teaching, impacting thereby the teaching-learning process to undergo a structural change. Among various pedagogical techniques that have been adopted, organizing synchronous classes has been found to be the most beneficial. It simulates the classroom environment, facilitating thereby parallel knowledge dissemination to a broader audience. This study measures the efficacy of synchronous web-based learning during this ongoing pandemic, among postgraduate Library and Information Science (LIS) students of Bangladesh. Using an online questionnaire, a survey was conducted among the postgraduate students of the Department of Information Science Library Management (ISLM) of the University of Dhaka. The results revealed that limitation of internet data, unstable internet, along with power blackouts were some of the primary inhibitors blocking the participants to attend classes online. Finally, this study concludes that as most students do not seem to be ready yet to study in a synchronous delivery mode, it recommends educational institutions in Bangladesh to provide an alternative delivery method, in order to sustain academic excellence in these challenging times.